Image processing and sensor based home energy saving [electronic resource] - Low, Kai Rui, 1993-; Imran Ghani, supervisor; Fakulti Komputeran (2016)
Project Paper (Sarjana Muda Sains Komputer (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2016